Chamilo 2.0: A Second Generation Open Source E-learning and Collaboration Platform - Maes, Jean-Marie (International Journal of Advanced Corporate Learning (iJAC), 2010)
Dokeos used to be one of the leading open source learning platforms. It is well known for the wide range of functions it offers and especially for its ease of use. In many ways it is however a typical first generation learning management system (LMS) consisting of a set of loosely integrated tools. The original design of this LMS has a number of serious drawbacks and limitations. Because of this it was decided to opt for a completely new system that would use state of the art development techniques. The new version is built on a repository of reusable simple and complex content objects, not only documents. The web LCMS is only one of the possible applications that run on that repository. One of the other applications that can make use of the same set of objects is the portfolio. Functions that used to be modules within a course can also simply be used as applications, e.g. forum, assessment, wiki. All functions such as creating, changing, editing and deleting an object are basically the same platform wide. As a result all modules and applications interact in a far more consistent and less bug prone way. This also greatly simplifies the user interface. This interface that is common to all objects in all tools and modules, makes a number of publication features available that were not available in all tools before, such as categorization, selection of target groups or users, visibility and period of publication. This is certainly adding to Chamiloâ??s ambition to be a user friendly, flexible, fast and consistent platform. The adaptability of the new system with integrated portal functions and a framework for web services makes it a suitable instrument not only for universities and schools, but also for the business world. In this way Chamilo offers a platform that is ready for future developments in a globalized world where life long learning and collaboration will be central.